HEAVY METALS CONCENTRATIONS IN WATER, SEDIMENT AND BIOTA IN KELABAT BAY, BANGKA ISLAND (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
Kelabat Bay is a semi enclosed waters divided into two parts, i.e., outer part of Klabat bay facing the Natuna Sea (T Luar) and inner Kelabat bay surrounded by human activities and five river mouths (T Dalam). Study on metal concentrations on sediments and biota was carried out in March and July 2006. Water and sediment samples as well as biota were analyzed using Flame-Atomic Absorption Spectrophotmetry (Flame AAS). The result showed that concentrations of the dissolved heavy metals were generally low with ranged as follows, Pb(1,0 – 26,0 μg L-1), Cd(